Everyday dorie ebook The way i cook. - Greenspan, Dorie (2018)
2019 James Beard General Cookbook Award Finalist To the hundreds of thousands who follow her on Twitter, Instagram, and Facebook, Dorie Greenspan's food is powerfully cookable—her recipes instant classics. In Everyday Dorie, she invites readers into her kitchen to savor the dishes that she makes all the time, from Miso-Glazed Salmon to Lemon Goop. What makes a "Dorie recipe"? Each one has a small surprise that makes it special. Mustard and walnuts in the cheese puffs. Cherry tomatoes stuffed into red bell peppers and oven-charred. Cannellini beans in cod en papillote. The dishes are practical, made with common ingredients from the supermarket, farmers' market, or pantry, like Sweet Chili Chicken Thighs, which is both weeknight simple and fine enough for company, and Eton Mess, a beautifully casual dessert of crumbled meringue, fruit, and whipped cream. They are easygoing, providing swaps and substitutions. They invite mixing and matching. Many can be served as dinner, or as a side dish, or as an appetizer, or hot, cold, or room temperature. And every single one is like a best friend in the kitchen, full of Dorie's infectious love of cooking and her trademark hand-holding directions.